The potential contribution of biogas to the security of gas supply in Germany - Daniela Thrän; Karen Deprie; Martin Dotzauer; Peter Kornatz; Michael Nelles; Kai Sven Radtke; Harry Schindler (Energy, Sustainability and Society, 2023)
Abstract Background Germany is highly dependent on natural gas, the availability of which has become uncertain due to Russia's invasion of Ukraine. Biogas provision in Germany is realized by more than 9500 mainly farm-side biogas plants that have the potential to increase the security of gas supply. Main text To assess the potential contribution of biogas to a secure gas supply in Germany, we combine a literature-based analysis of the current status and potentials of the biogas supply chain with calculations of the marginal costs for producing biogas under the current market conditions. Biogas provided 50 TWh of final energy in Germany in 2021, primarily in the form of power and heat. The production of biomethane, which can in principle replace natural gas when fed into the gas grid, amounted to 10 TWh in terms of the lower heating value, which corresponds to a share of about 1% of the German gas market in 2021. However, at the end of 2021, biogas significantly contributed to the provided power (13 TWh or 22% of power supply from natural gas) combined with co-generated heat (13 TWh or 2% of heat supply from natural gas). Increasing flexible power provision from biogas is promising under the current power market conditions. In contrast, the current biogas substrate mix will lead to crucial limitations: 75% of the input into German biogas are energy crops, which are limited in availability under rising agricultural prices. Conclusions and recommendations In conclusion, biogas can only make up a small share of the current natural gas consumption. An immediate programme to mobilize the use of biogenic by-products, waste, and cultivated biomass without requiring additional land is recommended. We also propose measures to increase the flexibility of power production and heat use and more greenhouse gas-related incentives of biogas supply for the medium term. Finally, we see the need for additional efforts for non-food feedstock mobilization on a European scale by realizing the envisaged tenfold increase in the contribution of biomethane to a production goal of 35 billion cubic metres by 2030 in the REPower EU Plan of the European Commission.